ANALISIS KARAKTERISTIK KEDALAMAN HUJAN DAN IKLIM DI PULAU LOMBOK - I WAYAN YASA; YUSRON SAADI; HERI SULISTYONO; ERY SETIAWAN; HARTANA HARTANA; I DEWA GEDE JAYA NEGARA (Universitas Mahasaraswati K. Mataram, 2021)
Climate and rain parameters are important factors that affect the availability of water resources on the earth's surface. The phenomenon of climate change that occurs today has an impact on the depth and distribution of rain and climatological parameters. The existence of rain and climate on Lombok Island changes very significantly every year. These changes affect various sectors, especially the irrigation sector. Thus, various adjustments must be made, such as adjusting the time of planting, cropping patterns and the types of plants being cultivated. In this case, knowledge about the characteristics of rain and climate that occurs on the island of Lombok is very important to know the pattern and magnitude of the incident as well as the time of the incident. This study was conducted to determine the condition of each climate variable in the Lombok island region by calculating the monthly average for 25 years. The smoothing uses the Theissen polygon method by utilizing 19 scattered rain station data and 4 climatological stations. Based on the analysis carried out, the results showed that the average monthly temperature ranged from 26.17-27.09°C, humidity 87.70-89.83%, sunlight 39.79-69.44%, and wind speed 53 ,73-110,21knot. The highest rainfall occurred in January of 235.33 mm, while the lowest occurred in August of 18.12 mm.